The innovative CIO and e-Participation in e-Government initiatives - Obi, Toshio (Global e-governance series, 2010)
Senior information executives are currently confronted by a continually growing and increasingly complex set of challenges. These include rapidly changing technologies, environmental issues and the current global economic situation. This book, volume 3 in the Global E-Governance Series, brings together the contributions of acknowledged experts from all over the world, who have presented papers and participated in discussions at three recent conferences on e-government, the role of the CIO (Chief Information Officer) and e-governance. They give us their frank and honest insights, and share with.